Bubble Evolution Around Heterogeneities in Phi(4)-Field Theories - Marin-Medina, J (SPRINGER, 2021)
Localised heterogeneities have been recently discovered to act as bubblenucleation sites in nonlinear field theories. Vacuum decay seeded by black holes is one of the most remarkable applications. This article proposes a simple and exactly solvable phi(4) model to study bubble evolution about a localised heterogeneity. Bubbles with a rich dynamical behaviour are observed depending on the topological properties of the heterogeneity. The linear stability analysis of soliton-bubbles predicts oscillating bubbles and the insertion of new bubbles inside an expanding precursor bubble. Numerical simulations in 2+1 dimensions are in good agreement with theoretical predictions.
Keywords: Topological Field Theories; Effective Field Theories